2009
DOI: 10.1007/s00221-009-1922-2
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive target matching asymmetries in left-handed individuals

Abstract: In right-handers, the ability to reproduce proprioceptive targets has been shown to be asymmetric, favoring the non-preferred left arm. The present study sought to determine whether a similar arm/hemisphere asymmetry exists for left-handers. Ten strong left-handed adults used the left or right arm to perform proprioceptive target matching tasks that varied in processing demands (i.e., need for memory, interhemispheric transfer) and target amplitude (20, 40 degrees). Similar to right-handers, left-handed indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
57
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 42 publications
7
57
2
Order By: Relevance
“…This trend is well in line with some literature, suggesting proprioceptive processing advantages of the nondominant limb in some conditions,12,16,5155 while others suggest gain differences of sensory-motor loops as an explanation 56. In contrast to those studies, other groups did not identify any difference between dominant and nondominant limb 18,22.…”
Section: Discussionsupporting
confidence: 91%
“…This trend is well in line with some literature, suggesting proprioceptive processing advantages of the nondominant limb in some conditions,12,16,5155 while others suggest gain differences of sensory-motor loops as an explanation 56. In contrast to those studies, other groups did not identify any difference between dominant and nondominant limb 18,22.…”
Section: Discussionsupporting
confidence: 91%
“…The dynamic dominance hypothesis (Sainburg 2005) argues that the dominant limb is important for the control of movement trajectory, while the nondominant limb is important for the control of limb position. This pattern has been shown to be the opposite in left-handed individuals in studies looking at both visuomotor adaptation (Wang and Sainburg 2006) and proprioceptive matching (Goble et al 2009). Additionally, investigations with stroke patients have also supported this theory (Schaefer et al 2007(Schaefer et al , 2009).…”
Section: Discussionmentioning
confidence: 98%
“…These differences in reach accuracy and precision across starting and final targethand locations may reflect the kind of signals the brain uses to derive the position of the proprioceptive target. Behavioral and neurophysiological research has revealed the existence of both static (i.e., position) and dynamic (i.e., movement) proprioceptive information, and that both types of information can be used separately to determine final limb position (Burke, Hagbarth, Lofstedt, & Wallin, 1976;Edin & Vallbo, 1990;Goble, Noble, & Brown, 2009;Imanaka, 1989;Imanaka & Abernethy, 1992a, 1992bLonn, Crenshaw, Djupsjobacka, Pedersen, & Johansson, 2000;Sittig, Denier van der Gon, & Gielen, 1985;Smeets & Brenner, 1995). However, previous research compared localization errors across starting positions of the hand and have not examined if the effect of starting position of the hand on localization errors varies across final target-hand locations.…”
mentioning
confidence: 98%
“…Redundant sensory information about an aspect of a stimulus (e.g., the location of a reaching hand) from two or more sensory sources can be integrated in such a way that a more accurate or precise estimate of that aspect is derived than would be possible with either source in isolation (e.g., Ernst & Banks, 2002;Kording & Wolpert, 2004;Snijders, Holmes, & Spence, 2007;Sober & Sabes, 2005;van Beers, Sittig, & Denier van der Gon, 1996, 1999. If the proprioceptive target moves immediately before a reach, the central nervous system (CNS) could integrate static and dynamic proprioceptive information about the target, forming a reliable estimate of target location based on proprioceptive information (e.g., Goble, Noble, & Brown, 2009). This information might then be used, weighted based on its reliability, along with visual information to determine final target location.…”
mentioning
confidence: 99%